Diffuse Reduction of Spleen Density Is an Independent Predictor of Post-Operative Outcomes After Curative Gastrectomy in Gastric Cancer: A Multi-Center Study - Huang, Yun-Shi; Chen, Xiao-Dong; Shi, Ming-Ming; Xu, Li-Bin; Wang, Su-Jun; Chen, Wei-Sheng; Zhu, Guan-Bao; Zhang, Wei-Teng; Shen, Xian (Frontiers in Oncology, 2020)
Objectives: The present study aimed to explore the association between spleen density and post-operative outcomes of patients after curative gastrectomy. Methods: From June 2014 to December 2015, we conducted a retrospective study to analyze pertinent clinical data from gastric cancer patients who underwent gastrectomy at the First and the Second Affiliated Hospital of Wenzhou Medical University. Spleen density was determined via computed tomography scans. Univariate and multivariate analyses were performed to determine the risk factors associated with post-operative outcomes after gastric cancer surgery. Results: Three hundred and ninety five patients were included, of whom 98 (24.8%) were defined as having a diffuse reduction of spleen density based on diagnostic cutoff values (spleen density ≤43.89 HU). Multivariate analysis revealed diffuse reduction of spleen density as an independent risk factor for post-operative complications and long-term overall survival. Conclusions: Spleen density can predict severe postoperative complications and long-term overall survival in gastric cancer patients. As an imaging evaluation method, spleen density is a novel tool can be used in clinical as a prognostic predictor for patients with gastric cancer.